The Hidden Risks of Perioperative Transfusions in Traumatic Lower Extremity Free Flap Reconstruction - Swiekatowski, Kylie R.; Manisundaram, Arvind D.; Woods, Delani E.; Green, Jackson C.; Bhadkamkar, Mohin A.; Wu-Fienberg, Yuewei (Journal of Reconstructive Microsurgery, 2024)
Background Blood transfusions have been associated with surgical complications; however, these studies are not specific to lower extremity (LE) reconstruction. We evaluated the effect of perioperative packed red blood cell (PRBC) transfusions on LE free flap outcomes in trauma patients.Methods Patients undergoing LE free flap reconstruction following acute injuries from 2016 to 2021 were retrospectively analyzed. The perioperative period for transfusions was defined as ± 3 days from the procedure. Parameters included demographics, perioperative characteristics, and outcomes. Major complications were complications requiring reoperation. Univariate and multivariate analyses were performed to identify associations.Results Of the 205 patients, 48% received PRBCs perioperatively. There was a trend toward higher major complications rate in the transfusion group (19 vs. 10%, p = 0.09). Wound size, injury severity score (ISS), and intraoperative estimated blood loss were greater in the transfusion group (p < 0.01). Preoperative hemoglobin/hematocrit were lower in the transfusion group (p < 0.001). Units of PRBCs transfused were independently associated with major complications on multivariate analysis (odds ratio [OR] = 1.34, confidence interval [CI]: 1.06–1.70, p = 0.015) and length of hospital stay (LOS; OR = 1.05, CI: 1.02–1.08, p = 0.002). Infection, wound size, ISS, and preoperative hemoglobin/hematocrit were independently associated with increased LOS (p < 0.05) but not with major complications.Conclusion The number of units of PRBCs given perioperatively was the only variable independently associated with major complications on multivariate analysis and was one of many variables associated with increased LOS. These findings suggest the usage of restrictive transfusion protocols in trauma patients requiring LE reconstruction.
Keywords: free tissue transfer; limb salvage; blood transfusion